2014
DOI: 10.5455/ijmsph.2014.260620142
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hazard awareness and safety practices among Nigerian sawmill workers

Abstract: Background: There is high prevalence of occupational injuries among blue-collar workers in the construction and other industry sectors whose jobs require high level risk in physical tasks. Aims & Objectives: The objective of this study was to assess the awareness of occupational hazards and safety practices among Nigerian sawmill workers. Materials and Methods: This cross-sectional survey recruited 94 sawmill workers comprising machine operators, planks pushers/carriers and planks vendors at Ile-Ife, Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
4
23
1
Order By: Relevance
“…21 Unlike our study, it was reported that majority of the workers (52.7%) in an automobile assembly plant in Kaduna, Nigeria were married, 19 also majority of the workers (72.0%) in a refinery at Kaduna were married.Also, majority of the workers (67.0%) in a sawmill in Ile-Ife, Nigeria were married. 22 This higher proportion of single respondents in this study may be because majority of the respondents are males and they are in the younger age group compared to the older age groups in the other studies cited.…”
Section: Discussionmentioning
confidence: 59%
“…21 Unlike our study, it was reported that majority of the workers (52.7%) in an automobile assembly plant in Kaduna, Nigeria were married, 19 also majority of the workers (72.0%) in a refinery at Kaduna were married.Also, majority of the workers (67.0%) in a sawmill in Ile-Ife, Nigeria were married. 22 This higher proportion of single respondents in this study may be because majority of the respondents are males and they are in the younger age group compared to the older age groups in the other studies cited.…”
Section: Discussionmentioning
confidence: 59%
“…Pre-testing of the questionnaire was carried out among 30 randomly selected sawmill workers in Offa Local Government Area of Kwara State. Data collected from the questionnaire were analyzed using SPSS 16.0 32% of the sawmill workers used PPE in Ilorin (10) and Ile-Ife (11) respectively. However, the utilization of PPE was much higher as reported by a study done in Ghana among workers of small scale sawmill workers where only 30% of the respondents never use any PPE (12).…”
Section: Discussionmentioning
confidence: 99%
“…Even though, compliance with many of the key safety practices was sub-optimal among the respondents in this study, the levels are relatively higher than those obtained in studies conducted among sawmill workers in other cities across Nigeria. [16][17][18] A study among sawmill workers in Ile-Ife, Nigeria, 16 reported that 72.3 to 79.8% of respondents have never utilized any safety device. Another study among sawmill workers in North-central Nigeria, 17 reported that less than 20% of participants wore protective devices.…”
Section: Discussionmentioning
confidence: 99%
“…Sawmill workers who have been in practice for at least 6 months and consented to participate in the study were considered eligible for this study. The sample size was estimated at 215 using the Fisher's formula for estimating minimum sample size for descriptive studies, 20 an 85.1% prevalence of awareness of at least one workplace hazard among sawmill workers from a previous study, 16 a precision level of 5% and an anticipated participant response rate of 95%. The eligible study subjects were selected by systematic sampling technique in the clusters of sawmills and wood shops in Sokoto metropolis, Nigeria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation